Strength of forest edge effects on litter‐dwelling macro‐arthropods across Europe is influenced by forest age and edge properties. Issue 6 (3rd March 2019) - De Smedt, Pallieter; Baeten, Lander; Proesmans, Willem; Van de Poel, Sam; Van Keer, Johan; Giffard, Brice; Martin, Ludmilla; Vanhulle, Rieneke; Brunet, Jörg; Cousins, Sara A.O.; Decocq, Guillaume; Deconchat, Marc; et al.
Abstract: Aim: Forests are highly fragmented across Western Europe, making forest edges important features in many agricultural landscapes. Forest edges are subject to strong abiotic gradients altering the forest environment and resulting in strong biotic gradients. This has the potential to change the forest's capacity to provide multiple ecosystem services such as nutrient cycling, carbon sequestration and natural pest control. Soil organisms play a key role in this perspective; however, these taxa are rarely considered in forest edge research. Location: A latitudinal gradient of 2, 000 km across Western Europe. Methods: We sampled six dominant taxa of litter‐dwelling macro‐arthropods (carabid beetles, spiders, harvestmen, centipedes, millipedes and woodlice) in forest edges and interiors of 192 forest fragments in 12 agricultural landscapes. We related their abundance and community composition to distance from the edge and the interaction with forest age, edge orientation and edge contrast (contrast between land use types at either side of the edge). Results: Three out of six macro‐arthropod taxa have higher activity‐density in forest edges compared to forest interiors. The abundance patterns along forest edge‐to‐interior gradients interacted with forest age. Forest age and edge orientation also influenced within‐fragment compositional variation along the forest edge‐to‐interior gradient. Edge contrast influenced abundance gradients of generalist predators. In general, older forest fragments, south‐oriented edges and edges along structurally more continuous land use (lower contrast between forest and adjacent land use) resulted in stronger edge‐to‐interior gradients while recent forests, north‐oriented edges and sharp land use edges induced similarity between forest edge and interior along the forest edge‐to‐interior gradients in terms of species activity‐density and composition. Main conclusions: Edge effects on litter‐dwelling macro‐arthropods are anticipated to feedback on important ecosystem services such as nutrient cycling, carbon sequestration and natural pest control from small forest fragments.